Crop identity and memory effects on aboveground arthropods in a long‐term crop rotation experiment. Issue 12 (29th May 2019) - Meyer, Michael; Ott, David; Götze, Philipp; Koch, Heinz‐Josef; Scherber, Christoph
Abstract: Agricultural landscapes are globally dominated by monocultures under intensive management. This is one of the main reasons for biodiversity loss and insect population decline in many regions all over the world. Agroecosystem biodiversity in these areas can be enhanced by cropping system diversification, such as crop rotations. Yet, long‐term studies on effects of crop rotations on aboveground agrobiodiversity are lacking. We set up a 10‐year long‐term crop rotation experiment in Central Germany and monitored the temporal dynamics of aboveground arthropods over a full cultivation period to investigate influence of current and preceding crop identity and cropping system diversification on activity density, species richness, and community structure. We found that species composition was strongly influenced by currently grown crop although effect on arthropods varied between species groups. Especially, winter oilseed rape strongly affects arthropod community structure. Interestingly, we were also able to show an influence of the preceding crops, indicating an ecological memory effect in the aboveground arthropod community. Our results show that crop identity of both currently and previously grown crops in crop rotations may lead to an increase in arthropod activity density and changes in species composition. Diversified crop rotations including appropriate crops can be an easily implemented tool to increase arthropod biodiversity and biomass at large spatial and temporal scales, particularly in areas dominated by a single crop (e.g., wheat, maize). Our results may help to design optimized crop rotations for large‐scale enhancement of insect biodiversity in agroecosystems. Abstract : We analyzed arthropod community in a long‐term crop rotation experiment. Crop identity and preceding crops strongly influenced community composition. Diversified crop rotations can enhance arthropod activity density in intensively used agroecosystems.